Regulation of neuronal autophagy and cell survival by MCL1 in Alzheimer's disease - Abdol-Hossein Rezaeian; Wenyi Wei; Hiroyuki Inuzuka (Compuscript Ltd, 2022)
Maintaining neuronal integrity and function requires precise mechanisms controlling organelle and protein quality. Alzheimer's disease (AD) is also characterized by functional defects in the clearance and recycling of intracellular components. In fact, neuronal homeostasis involves autophagy, mitophagy, apoptosis, and compromised activity in these cellular processes may cause pathological phenotypes of AD. Therefore, mitophagy is a critical mitochondrial quality-control system, and impaired mitophagy is a hallmark of AD. Myeloid cell leukemia 1 (MCL1), a member of the pro-survival B-cell lymphoma protein 2 (BCL2) family, is a mitochondrially targeted protein that contributes to maintaining mitochondrial integrity. Mcl1-knockout mice display peri-implantation lethality. Studies on conditional Mcl1-knockout mice have demonstrated that MCL1 plays a central role in neurogenesis and neuronal survival during brain development. Accumulating evidence indicates the critical role of MCL1 as a regulator of neuronal autophagy, mitophagy, and survival. In this review, we discuss the emerging neuroprotective function of MCL1 and how dysregulation of MCL1 signaling is involved in the pathogenesis of AD. Because members of the pro-survival BCL2 family proteins are promising targets of pharmacological intervention with BH3 mimetic drugs, we also discuss the promise of MCL1-targeting therapy in AD.